2014
DOI: 10.1371/journal.pone.0113721
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the Secretory Function of Irradiation-Damaged Salivary Gland by Administrating Deferoxamine in Mice

Abstract: ObjectivesOne of the major side effects of radiotherapy for treatments of the head and neck cancer is the radiation-induced dysfunction of salivary glands. The aim of the present study is to investigate the efficacy of deferoxamine (DFO) to restore the secretory function of radiation-damaged salivary glands in mice.MethodsDFO (50 mg/kg/d) was administered intraperitoneally in C57BL/6 mice for 3 days before and/or after point-fixed irradiation (18 Gy) of submandibular glands. The total 55 mice were randomly div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In fact, similar pathologies are associated with diseases that result in xerostomia, such as Sjögren's syndrome and irradiation damage as a result of treatment of head and neck cancers, suggesting that a continued interaction of the vasculature and the epithelium may be a component of homeostasis or a response to injury in adult glands. Consistent with our findings in development, several studies have suggested that the vasculature is damaged in salivary gland pathologies and that gland regeneration is enhanced by restoration of the vasculature (Cotrim et al, 2007;Zhang et al, 2014;An et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, similar pathologies are associated with diseases that result in xerostomia, such as Sjögren's syndrome and irradiation damage as a result of treatment of head and neck cancers, suggesting that a continued interaction of the vasculature and the epithelium may be a component of homeostasis or a response to injury in adult glands. Consistent with our findings in development, several studies have suggested that the vasculature is damaged in salivary gland pathologies and that gland regeneration is enhanced by restoration of the vasculature (Cotrim et al, 2007;Zhang et al, 2014;An et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Zhang et al . found that irradiated mice treated with DFO showed increased healing and function of salivary glands22. Elevated HIF-1α levels lead to an upregulation of VEGF, as well as several other genes, such as erythropoietin, increased cell survival, and glycolysis2324, which would in turn lead to improved healing.…”
Section: Discussionmentioning
confidence: 98%
“…According to several previous studies it leads to side effects such as apoptosis of acinar cells and their loss that in turn results in reduction of saliva production and thus xerostomia. However, the detailed mechanisms of radiation-induced xerostomia remain unclear (Lim et al 2013 ; Zhang et al 2014 ). Since CD44 has been shown to be expressed in acinar epithelial cells of SG, we performed immunostaining for CD44 to assess severity of acinar cell damage as an indicative parameter for SG hypofunction after IR.…”
Section: Discussionmentioning
confidence: 99%